The potential of hormones and selective oestrogen receptor modulators in preventing voiding dysfunction in rats - Tantiwongse, Kavirach (2008)
OBJECTIVE: To investigate whether oestrogen, selective oestrogen receptor modulators (SERMs), and growth hormone (GH) can prevent the development of voiding dysfunction in a postpartum postmenopausal rat model of voiding dysfunction. MATERIALS AND METHODS: Immediately after spontaneous delivery, nine primiparous Sprague-Dawley rats served as uninjured controls (sham group) and 54 underwent intravaginal balloon dilation. On day 7, the 54 subject rats underwent bilateral ovariectomy. A week later, six treatment groups of nine rats were randomized to receive: normal saline (injured control group), 17β-oestradiol (E(2)), raloxifene, levormeloxifene, GH, or GH + E(2). The treatment groups received daily subcutaneous injections for 3 weeks. The effects of hormone treatment were examined by conscious cystometry at the end of the study. Voiding dysfunction was defined to include overactive bladder and sphincter deficiency. RESULTS: The sham rats had a mean (SD) voiding frequency of 3 (0.87) times in 10 min and a bladder capacity of 0.43 (0.13) mL with smooth cystometry curves. The number of rats in each treatment group (each group contained nine rats) that had voiding dysfunction was as follows: E(2), three; raloxifene, six; levormeloxifene, four; and controls, four (P > 0.05 among the groups). Only one rat in the GH-treated group and no rats in the GH + E(2)-treated group had voiding dysfunction, which was significantly less in the GH + E(2)-treated group than in the controls (P = 0.041). CONCLUSION: This functional data suggest that the development of voiding dysfunction can be prevented by short-term administration of GH and GH + E(2) in our rat model. SERMs and E(2) alone seem to have no therapeutic effect.